DDX39 Overexpression Predicts a Poor Prognosis and Promotes Aggressiveness of Melanoma by Cooperating With SNAIL - Xing, Chengjuan; Tian, Hui; Zhang, Yini; Guo, Kun; Tang, Ying; Wang, Qimin; Lv, Li; Wang, Lifen (Frontiers in Oncology, 2020)
This study aimed to investigate the prognostic value and molecular mechanism of DDX39 and its effector SNAIL in melanoma. First, overexpression of DDX39 in melanoma, which was identified by database analysis, was further validated in patient tissues. Cell growth, cell cycle, cell migration, and cell invasion assays were then performed to evaluate the effects of downregulated DDX39 on the melanoma cell proliferation and aggressiveness. The same approaches were also used to reveal the cooperation of the transcription factor SNAIL with DDX39 to promote the aggressiveness of melanoma cells. We found that the expression of DDX39 was significantly upregulated in melanoma tissue compared to pigmented nevus tissue, and it was positively correlated with the clinical stage defined by the American Joint Committee on Cancer (AJCC) and the prognosis. Downregulation of DDX39 in melanoma cells was found to significantly inhibit cell proliferation, increase G2/M cell cycle arrest, enhance caspase-mediated cell apoptosis, and suppress cell invasion and migration. In addition, we demonstrated that the overexpression of SNAIL could restore the cell growth and aggressiveness impaired by DDX39 RNA interference. Immunohistochemical staining also showed a positive correlation between DDX39 overexpression and SNAIL overexpression in melanoma tissues, suggesting that SNAIL is one of the effectors activated by DDX39. In summary, the overexpression of DDX39 and SNAIL was positively related to the poor prognosis of melanoma patients and the increased aggressiveness of melanoma cells. Our study provides valuable evidence regarding the prognostic value of DDX39 and SNAIL as well as their potential as novel therapeutic targets for treating melanoma patients.